Discrimination Distress During Adolescence - Fisher, Celia B.; Wallace, Scyatta A.; Fenton, Rose E. (Journal of Youth and Adolescence, 2000)
Amidst changing patterns of accommodation and conflict among American ethnic groups, there remains a paucity of research on the nature and impact of racial and ethnic discrimination on development in multiethnic samples of youth. The Adolescent Discrimination Distress Index along with measures of caregiver racial bias preparation and self-esteem was administered to 177 adolescents drawn from 9th–12th graders self-identified as African American, Hispanic, East Asian, South Asian, and non-Hispanic white. Youth from all ethnic backgrounds reported distress associated with instances of perceived racial prejudice encountered in educational contexts. Instances of institutional discrimination in stores and by police were higher for older youth and particularly for African American and Hispanic teenagers. Encounters with peer discrimination were reported most frequently by Asian youth. Reports of racial bias preparation were associated with distress in response to institutional and educational discrimination and self-esteem scores were negatively correlated with distress caused by educational and peer discrimination. The importance of research on discrimination distress to understanding adolescent development in multiethnic ecologies is discussed here.